HAK WARIS BAGI ISTRI YANG DITALAK BAIN OLEH SUAMI YANG SEDANG SEKARAT PERSPEKTIF MAZHAB MALIKI DAN SYAFI’I - Ainun Mardiah (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2018)
Talak is a halal word but is hated by God, because it can only happen if in a household there is a conflict that can no longer be resolved and as a last resort for domestic life. Because of that there was adivorce that was dropped by the husband when he was dying and later died. In the event of a death, theproblem arises from the transfer of property from people who have died to people who are still alive. Inrelation to inheritance law, the wife who was dropped by the husband when he was dying and then diedthere was a difference of opinion between Imam Malik and Imam Shafi'i. The opinion of Imam Malik inthe books of al-Muwaththa 'and al-Mudawwanatul Kubra that his wife received inheritance. Whereas theopinion of the Qaul Jadid version of Shafi'i in the book al-Umm and the book Mughni Muhtaj that hiswife did not inherit absolutely.